Validation of an efficient shear-flexure interaction model for planar reinforced concrete walls. (1st February 2022) - López, Carlos N.; Massone, Leonardo M.; Kolozvari, Kristijan
Highlights: E-SFI captures accurately the response of slender and squat walls. Global and local responses are well estimated. The model captures the impact of different wall characteristics and properties. Abstract: This research extensively validates an efficient macro-modeling approach for simulating the nonlinear response of planar reinforced concrete walls. The analytical model, named as Efficient Shear Flexure Interaction (E-SFI), which is based on the Shear-Flexure Interaction Multiple-Vertical-Line-Element-Model (SFI-MVLEM), is used in the present work. The E-SFI model incorporates a calibrated expression to compute the horizontal normal strain ε x ; thus, the additional degree of freedom per RC panel element is removed from the SFI-MVLEM formulation, obtaining only six degrees of freedom per element, similarly to common fiber-based models. To validate the model, an extensive shear strength database of 252 RC wall specimen tests reported in the literature was used, obtaining an average ratio of the predicted over the experimentally measured shear strength ( V model / V test ) of 1.04 with a coefficient of variation of 0.23, indicating an accurate estimation of the shear strength with a relatively small dispersion. Also, the analytically predicted and the experimentally measured hysteretic response were compared for ten densely instrumented RC wall specimens reported in the literature, for a shear span-to-depth ratio ranging from 0.44 to 3.0, under single or double curvature conditions, revealing an accurate prediction of the global, flexural, and shear responses for all wall specimens.